Industrialization "without" tariffs: Friedrich List as a forerunner of modern Development Economics - Jose Pedro Pontes; Armando J. Garcia Pires (European Regional Science Association (ERSA), 2015)
In this paper, we analyse Friedrich List's contribution to the modern theory of economic development. We argue that Friedrich List saw economic development as a combination of a sectorial division of labour (following Adam Smith, 1776) and a geographical division of labour across regions and countries. In this sense, the passage from a traditional economy to an industrial one consists of balanced growth at both the sectorial and geographical level, as we see in modern development economics (see Rosentein-Rodan, 1943; and Murphy et al., 1989). In addition, List highlights the role of transport costs in the industrialization process not only in terms of the costs incurred by firms, but also how industrialization affects these costs, since modern technology produces goods that are ?lighter? to transport than goods produced with traditional technology. In this sense, contrary to what is usually attributed to List, tariffs are not the central part of his argument for industrialization. He puts more emphasis on the creation of a larger internal market via for instance a customs union and the complementarities between resources and sectors in a country. We illustrate these arguments with a model.
Keywords: O14; R11; R30; 330; Friedrich List; Economic Development; Industrial Agglomeration; Labor Division